2022
DOI: 10.3390/cancers14071725
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Tissue Compression Identifies High-Grade Glioma Patients with Reduced Survival

Abstract: The compression of peritumoral healthy tissue in brain tumor patients is considered a major cause of the life-threatening neurologic symptoms. Although significant deformations caused by the tumor growth can be observed radiologically, the quantification of minor tissue deformations have not been widely investigated. In this study, we propose a method to quantify subtle peritumoral deformations. A total of 127 MRI longitudinal studies from 23 patients with high-grade glioma were included. We estimate longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…MRE probes the shear properties of tissue, while the probing by surgical tools involves a more complex process, as the tissue could also be compressed and compromised. Furthermore, tumor growth can compress surrounding tissue, generating solid stress due to swelling 47,48 . Several studies have found that MRE is sensitive to compressive stress 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…MRE probes the shear properties of tissue, while the probing by surgical tools involves a more complex process, as the tissue could also be compressed and compromised. Furthermore, tumor growth can compress surrounding tissue, generating solid stress due to swelling 47,48 . Several studies have found that MRE is sensitive to compressive stress 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…The compression of healthy peritumoral tissue in brain tumor patients is considered a major cause of life-threatening neurological symptoms. After examining longitudinal MRI studies of patients with HGG, Fuster-Garcia et al published a methodology for quantifying subtle peritumoral deformations and relating them to patient overall survival (OS) (Figure 3A,B) (Table 1) [31]. As expected, lower tumor compression on surrounding tissues was associated with greater patient survival.…”
Section: Major Finding Experimental Systemmentioning
confidence: 92%
“…229 MRI exams from 27 patients with histologically confirmed HGG. [31] APTw MRI imaging shows good scan-rescan reproducibility in healthy tissue and tumors.…”
Section: Mrimentioning
confidence: 97%
“…Consistent with prior work 24,38,42,[55][56][57] , all MRI-derived maps were normalized to reference tissue using NordicIce. As BM encompass both grey matter (GM) and white matter (WM), reference tissue was defined by the WM and GM masks 22,30,42,[58][59][60][61][62] , excluding areas with contrast enhancement and abnormal T2weighted/FLAIR hyperintensity. All analyses were performed with normalized values 38,[55][56][57]63 , which is a unit-less ratio of absolute voxel values to the reference tissue.…”
Section: Image Processingmentioning
confidence: 99%